Implementation of Saliling Policy as Fulfillment of The Right to Health Services for People with Mental Disorders in Preventing Shackling in South Kalimantan Province - Insani, Dina Aulia; Simandjutak, Marcella Elwina; Dhanardhono, Tuntas (Universitas Katolik Soegijapranata Semarang, 2024)
Mental health is a basic human right for every citizen without exception. In Indonesia, psychiatric hospitals are still uneven, as are the psychiatrists and health workers specialized in mental health. Mental health services and the rights of patients with mental illnesses are still not optimal, as a result, many patients with mental illnesses experience shackles. Sambang Lihum Psychiatric Hospital initiated the public service innovation program, namely Saliling (Sambang Lihum Keliling). The purpose of this study is to determine the regulation and implementation of the Saliling policy as the fulfillment of mental health service rights in South Kalimantan Province, explore the implementation in preventing and reducing shackling, as well as inhibiting policy. The research method used is descriptive-analytic with a sociological juridical approach that examines Sailing policies.The study concludes that legal protection of patients mental illness right to health services and prevention of shackling through Saliling policies can be fulfilled. The legal basis for the right to mental health services and shackling prevention is the health law and the Minister of Health Regulation. The main inhibiting factor is the amount of budget, human resources, and program schedule.Abstrak: Kesehatan merupakan hak dasar bagi setiap warga negara tanpa terkecuali termasuk kesehatan jiwa. Jumlah fasilitas kesehatan tingkat lanjut terutama rumah sakit jiwa (RSJ) masih tidak merata di Indonesia, begitu pula dengan jumlah dokter spesialis kedokteran jiwa. Belum optimalnya pelayanan kesehatan jiwa dan belum terjaminnya hak ODGJ dapat mengakibatkan kasus Pasung. RSJ Sambang Lihum menggagas Program inovasi pelayanan publik yaitu Saliling. Program inovasi Saliling RSJ Sambang Lihum ditetapkan sebagai program untuk memberikan pelayanan kesehatan jiwa langsung pada masyarakat yang membutuhkan dan dilaksanakan untuk mencegah pasung.Tujuan penelitian ini untuk mengetahui pengaturan dan implementasi kebijakan Saliling sebagai pemenuhan hak pelayanan kesehatan bagi ODGJ di Provinsi Kalimantan Selatan, mengetahui dan mengeksplorasi implementasi kebijakan dalam mencegah dan mengurangi Pasung, serta mengetahui faktor-faktor penghambat maupun pendukung. Metode pendekatan yuridis sosiologis yang mengkaji implementasi Kebijakan Saliling.Hasil penelitian menunjukkan secara nasional pengaturan dan kebijakan pemenuhan hak pelayanan kesehatan bagi ODGJ telah ada. Perlindungan hukum terhadap pasien terutama ODGJ untuk mencegah pasung, RSJ Sambang Lihum secara khusus telah mengeluarkan Kebijakan Saliling. Kebijakan ini melibatkan lintas sektor sehingga dapat memenuhi jangkauan pelayanan kesehatan jiwa dalam rangka mencegah pasung. Kendala yang masih menjadi faktor penghambat utama adalah pada faktor teknis yaitu jumlah anggaran, SDM dan waktu pelaksanaan